Problematic soil mechanics in the Algerian arid and semi-arid regions: Case of M’sila expansive clays - Khemissa, Mohamed; Mahamedi, Abdelkrim; Mekki, Lakhdar (Journal of Applied Engineering Science & Technology; Vol 1 No 2 (2015), 2015)
This paper presents a state-of-the art review on the behavior of problematic soils in arid and semi-arid regions in Algeria, where significant damages frequently appear affecting the road infrastructures, roadway systems and various networks and other small civil and industrial constructions. It deals with characterization and treatment experimental studies on some Algerian expansive natural soils, including those conducted on M’sila expansive clays.
Keywords: Arid and semi-arid regions, Problematic soil, Expansive clay, Compaction, Treatment with hydraulic binders, Bearing